In Vitro Propagation of Buah Merah (Pandanus Conoideus Lam) Through Lateral Bud Proliferation - Imelda, Maria; Wulansari, Aida; Sumarnie, Sumarnie (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2008)
Pandanus conoideus Lam or Buah merah of the Pandanaceae is native to East Indonesia, particularly Papua and North Maluku. Traditionally the fruits are used for health promotion and maintenance as well as for curing several illnesses. Recently, it has been reported that the fruits are potential for cancer medication . As a result, there has been an overexploitation of the plants from their habitats . In order to anticipate their possible disappearance due to overexploitation in the wild, an efficient and effective technology for the mass propagation, conservation and cultivation of these plants should be developed. Generally buah merah is propagated vegetatively by offshoots and stem cuttings or generatively by seeds. Micropropagation has many advantages over the conventional method. because the technique allows mass cIonal and pathogen-free production of plants at high rate of multiplication all year round . In this research the effects of 0,1 -0.2 mg/l thidiazuron (TDZ), 0.5- 1.0 benzyl amino purine (BAP) and 0.25-0.5 mg/l Kinetin (KN) on shoot bud induction and proliferation of P. conoideus were investigated using nodal sections or lateral buds or P. conoideus on modified Murashige and skoog medium. Shoots were rooted on MS medium without plant growth regulators (PGR) . The result showed that lateral buds of Pandanus started to initiate growth after 4-7 days in culture. The best medium for shoot proliferation was MS containing either 0,5 mg/l BAP with 0.1 mg/ l TDZ or I mg/l BAP with 0.5 mg/I KN. giving a multiplication rate of I6.5 shootlets per shootbud explant after 8 weeks Rooting of shoots was successfully conducted on MS medium without PGR. Acclimatization of rooted plantlets was achieved on a mixed medium of cocopeat and soil (1:1). Keywords: Buah merah (Pandanus conoideus). lateral buds, BAP. TDZ. KN